PENERAPAN MODELPEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VSDN4 SUNGAI SIPUT KECAMATAN SIAK KECILKABUPATEN BENGKALIS - Irma Yuniati; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abtract : The research was conducted with the aim to improve learning outcomes fifth grade science students SDN 4 River Snail Bengkalis District of Siak Kecil. The school year 2014/2015. IPA learning outcome can be viewed through the